PENGARUH KEBIASAAN BELAJAR DAN LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Riskyka (LPPM STKIP AL MAKSUM, 2021)
The purpose of this study was to determine how study habits affect student learning outcomes in mathematics subjects at Al Maksum Stabat Private Junior High School, to find out how the family environment affects student learning outcomes in mathematics subjects at Al Maksum Private Junior High School Stabat, and to determine the effect of study habits. students and the family environment on student learning outcomes in mathematics at Al Maksum Stabat Private Junior High School. The population in this study were all eighth grade students of Al Maksum Stabat Private Junior High School, 98 students. Then 2 classes were selected from 3 classes. Data collection techniques in the form of observation, and questionnaires. The data analysis method used is multiple linear regression analysis using the SPSS program. The results showed that the significant value of study habits had an average value (M) of 36.63 which was in the 34-41 interval with the